2019
DOI: 10.1111/ecc.13131
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis: Exercise intervention for sleep problems in cancer patients

Abstract: Background Sleep problems cause physical and mental distress and may influence the survival of cancer patients. Objectives This study aimed to explore the efficacy of exercise intervention to improve sleep in cancer patients. Methods Published papers from 1980 to 2018 were searched. Results The major findings included (a) exercise intervention had small positive effects on enhancing total subjective sleep quality (TSSQ; g = 0.38, 95% CI = 0.21–0.54) and objective sleep onset latency (g = 0.21, 95% CI = 0.01–0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 51 publications
2
29
1
Order By: Relevance
“…While less well studied and often evaluated as a secondary outcome, [35][36][37][38] the available evidence suggests that regular exercise results in decreases in sleep disturbance. In our study, all of the exercise groups had scores for the majority of the GSDS subscales, as well as the total score, that were above the clinically meaningful cutoffs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While less well studied and often evaluated as a secondary outcome, [35][36][37][38] the available evidence suggests that regular exercise results in decreases in sleep disturbance. In our study, all of the exercise groups had scores for the majority of the GSDS subscales, as well as the total score, that were above the clinically meaningful cutoffs.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of fatigue, across several systematic reviews and meta-analyses of patients undergoing active treatment as well as cancer survivors, [26][27][28][29][30][31][32][33][34] the findings suggest that multimodal exercise interventions that include aerobic, resistance, and stretching exercises are effective in decreasing fatigue. While less well studied and often evaluated as a secondary outcome, [35][36][37][38] findings from four systematic reviews suggest that regular exercise results in decreases in sleep disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…Spreadsheets were created according to CONSORT guidelines, and the reviewers used these spreadsheets to extract information about the characteristics, study population, eligibility criteria, intervention methods, and the results reported (Shulz et al, 2010;Falci and Marques, 2015). Each article was reviewed twice by the researchers to guarantee the reliability of the results (Moher et al, 2009a).…”
Section: Data Extractionmentioning
confidence: 99%
“…The quality of original works was assessed carefully based on the physical training results in WSBC. Articles with a low risk of bias were used (percentual ≥ 80), as determined by the CONSORT guidelines; methodological quality, as well as the inclusion and exclusion criteria, statistical data, and results, was also verified 1 (Shulz et al, 2010;Falci and Marques, 2015).…”
Section: Quality Assessment Of Individual Studiesmentioning
confidence: 99%
See 1 more Smart Citation